2020
DOI: 10.3390/land9070216
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Territorial Heritage of Declining Rural Areas in Spain: Towards Integrating Top-Down and Bottom-Up Approaches

Abstract: The population of a considerable number of rural areas in the interior of Spain is in decline. Faced with this problem, various institutions are launching initiatives to enhance the territorial heritage (natural and cultural) of these areas and, starting with a minimum of economic diversification, help to reverse these depopulation processes and promote local development overall. Two specific initiatives are analysed here: the Almadén Mining Park and the Molina-Alto Tajo District Geopark, both of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…As stated at the beginning of this work, the revitalization of rural areas through means of economic diversification, improvement in the quality of life, inter-sectoral cooperation, and demographic stabilization are some of the core objectives of CLLD [4]. Thus LEADER aims to use its specific characteristics to complement the traditional CAP aids and even to serve as an alternative to them in the most rural and remote areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated at the beginning of this work, the revitalization of rural areas through means of economic diversification, improvement in the quality of life, inter-sectoral cooperation, and demographic stabilization are some of the core objectives of CLLD [4]. Thus LEADER aims to use its specific characteristics to complement the traditional CAP aids and even to serve as an alternative to them in the most rural and remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…They point toward a territorial imbalance in the distribution of economic resources, as the more developed municipalities, with an already existing business infrastructure can attract more investment funds compared to the more economically disadvantaged areas. Thus, in the early 1990s, the EU started to look for alternative solutions in the form of participative approaches and in the development of social capital as driving forces for the revitalization of rural communities [4]. One such solution was LEADER ("Liaison Entre Actions de Développement de l'Économie Rurale"), which became one of the most important alternative bottom-up rural development methods used in the EU in the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…Successful examples all around the world have shown that former mining areas can be reused to provide social, ecological, and economic benefits [13,57]. Some mines have become touristic attraction points (Kansas, Texas, USA; Wieliczka, Poland), public parks (Konya, Turkey; Lawrence, MA, USA), stadiums (Braga, Portugal), solar power plants (Senftenberg, Germany) or UNESCO sites (Rosas mines in Sardinia-Italy, Almaden Mining Park in Spain, Falun Mine in Sweeden, Cornwall and West Devon in the UK) [13,[58][59][60][61]. But for these transformations to take place, large projects approved by authorities and supported by governments need to be considered.…”
Section: Revitalization Opportunities For Future Development Pathsmentioning
confidence: 99%
“…Local governments must develop special policy strategies for attracting businesses to utilize these resources. In addition, merely depending on government-led planning is not enough [26,27]. It is necessary to introduce market forces from metropolitan regions to coordinate diversified stakeholders and to form a "growth alliance" for rural revival [28][29][30].…”
Section: Introductionmentioning
confidence: 99%